2007
DOI: 10.1080/02635140701250857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of instruction based on conceptual change activities on students’ understanding of static electricity concepts

Abstract: This study was conducted to investigate the effectiveness of learning activities based on conceptual change conditions and traditionally designed physics instruction on tenth-grade students' understanding of static electricity concepts and their attitudes toward physics as a school subject. Misconceptions related to static electricity concepts were determined by related literature on this subject and interview with teachers who have been teaching static electricity for more than 5 years. Accordingly, the Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 63 publications
2
29
0
6
Order By: Relevance
“…The results of this study show that conceptual change texts may be an effective strategy for improving instruction and remedying students' alternative conceptions. The data gathered from the available literature also supports this view (Chambers & Andre, 1997;Mikkila, 2001;Tekkaya, 2003;Canpolat et al, 2006;Baser & Geban, 2007a;Baser & Geban, 2007b). In particular, the findings of Canpolat et al, (2006)'s are essentially parallel to this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this study show that conceptual change texts may be an effective strategy for improving instruction and remedying students' alternative conceptions. The data gathered from the available literature also supports this view (Chambers & Andre, 1997;Mikkila, 2001;Tekkaya, 2003;Canpolat et al, 2006;Baser & Geban, 2007a;Baser & Geban, 2007b). In particular, the findings of Canpolat et al, (2006)'s are essentially parallel to this study.…”
Section: Discussionsupporting
confidence: 87%
“…In the science education literature, there is an abundance of studies related to utilization of conceptual change texts (Wang & Andre, 1991;Hynd, Mcwhorter, Phares, & Suttles, 1994;Chambers & Andre, 1997;Mikkila, 2001;Yürük & Geban, 2001;Cakir, Uzuntiryaki, & Geban, 2002;Palmer, 2003;Tekkaya, 2003;Canpolat, Pinarbasi, Bayrakceken, & Geban, 2006;Baser & Geban, 2007a;Baser & Geban, 2007b). Wang and Andre (1991) and Chambers and Andre (1997) investigated the effect of conceptual change texts on students' understanding and showed that subjects who received a conceptual change text instruction significantly improved their performance in their understanding of electricity concepts as compared to traditional texts.…”
Section: The Effectiveness Of Conceptual Change Texts In Remediating mentioning
confidence: 97%
“…However, a radical change of the existing methods seems to be problematic for teachers in Thailand. This has also been found in other countries (White 1992;Baser and Geban 2007). There is also no substantial evidence at the upper secondary level that other teaching methods can effectively replace the traditional one.…”
Section: Introductionmentioning
confidence: 68%
“…This result confirmed the finding of Duit and Treagust (2003) which implied that attending advanced but traditional university physics course would not help students to improve their physics understanding. Başer and Geban (2007) also showed that misconceptions held by students before and after traditional physics instruction were the same. Hence, one cannot escape here from concluding that the traditional but high-level physics course would not help in conceptual physics learning.…”
Section: Discussionmentioning
confidence: 88%